Impact assessment of input and output market development interventions of the IPMS Project: The case of Alaba and Dale Woredas, SNNPR, Ethiopia - Getachew, Y. (Haramaya University, 2010)
Agricultural marketing is the main driving force for economic growth. But it is poorly developed in most developing countries. The main cause for the poor development of the agricultural production is the poor development of the agricultural marketing. To overcome this problem the government of Ethiopia has developed a master plan to enhance market oriented production. To realize this plan different projects have been developed and implemented in different parts of the country. Of these projects, Improving Productivity and Market Success of Ethiopian farmers’ is the one being implement by ILRI at 10 pilot learning Woredas in the country. Though it is implemented for about five years its impact has not been evaluated so far. This study therefore evaluates the impact of input and output market development interventions of the project at Alaba and Dale PLW, SNNPR on institutional and organizational, input use and productivity, total net income, marketed surplus and market orientation of the participant households. The study has used cross-sectional survey of 200 sample households which was taken from both Alaba and Dale intervention PAs. A propensity score matching method was applied to assess the impact of the project on outcome variables on the treated households. The intervention has resulted in positive and significant effect on level of input use on the treated households. This increased amount of input use made participants to earn on average a total net income of about birr 1,483 at Alaba and birr 2,228 at Dale form the commodities of intervention over the counter parts. It also enabled them to supply more produce to the market and to be market oriented. Based on the results obtained the continuity/ presence of such market development interventions (input and output) has a paramount importance for the achievement of development and transformation plan and the overall development endeavors of the country